PENGARUH BELANJA PEMBANGUNAN TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN DAN KESEJAHTERAAN MASYARAKAT KABUPATEN/KOTA PROVINSI PAPUA - Kasipmabin, Lidwina Lidia; Setiawina, Nyoman Djinar; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 ABSTRACT Financial Management through the Shopping District (Education, Health , Social and Community Empowerment Papua) that have not been used optimally and fully powered and sustained well-being of the people of Papua . This study aims to determine the effect of development expenses (social, health , education, empowerment of rural communities) to inequality of income distribution and welfare districts / cities province. The data used are secondary data obtained from the Central Statistics Agency (BPS) Papua and other related institutions. Analytical techniques used are strip analysis or path analysis and descriptive analysis. The results of this study showed that from 2010 up to 2012 the production of social government has a direct and significant influence on the inequality of income distribution of the society. Government spending in health has a direct influence on the inequality of income distribution and the welfare of society , but not significant. Education government spending and significant indirect effect on the well-being of society through the inequality of income distribution. Production government areas of community empowerment villages have a direct influence on the distribution of income inequality and welfare districts / cities Papua but not significant. There is no significant influence of the development expenses (social, health, education and empowerment of rural communities) to the welfare of society as a direct or indirect indication that the regional government prefers let the suitability or compatibility estimates, are estimates innovative optimization, as well as the political will and government's commitment to the allocation of production according to the needs of the community to improve the county budget to social well- being of society, health, education as well as the empowerment of rural communities can be increased according to the expected government over the years. Keywords: cost of development, inequality of income distribution, prosperity.
Keywords: cost of development, inequality of income distribution, prosperity